Why trigger warnings are beneficial, perhaps even necessary. Issue 2 (2nd July 2016) - Lockhart, Eleanor Amaranth
Abstract: In response to a panel discussion from the Eastern Communication Association (ECA) and the article written by Dr. Robert Vatz in this issue, I make a case for the usefulness and benefit of the practice of trigger warnings in the classroom. I draw on my own experience as a transsexual woman teaching at a conservative school, as well as contemporary psychological theory and ethics. I argue that trigger warnings are not detrimental to freedom of speech (as others, such as Dr. Vatz here, contend) and that they are in fact necessary for the well-being of some students. Moreover, judicial use of warnings can enhance classroom participation and discussion, and the intellectual development of students and faculty.